Qualitative study on experience of healthcare staff who have undergone a hybrid root cause analysis training programme - Yick-Ting Kwok; Alastair P Mah (BMJ Open Quality)
Background Root cause analysis (RCA) is a structured investigation methodology aimed at identifying systems factors to prevent recurrence of incidents. To enhance staff’s knowledge and skills, a hybrid RCA training course was conducted in February 2021. Overseas instructors conducted training online and local participants attended the training together physically with onsite facilitator support. This study aimed at understanding the experiences of trainees who have undergone the training, evaluated its effectiveness and identified opportunities to enhance RCA training quality in the future.Methods A qualitative study using virtual synchronous focus group interviews was conducted. Purposive sampling was adopted to invite all trainees from the RCA training course to join. A semistructured interview was used to guide the study participants to share their experiences. All groups were audio-recorded, transcribed verbatim and anonymised for data analysis.Results Overall, 6 focus groups with 19 participants were held between July and November 2021. Five key themes were identified including: (1) training contents, (2) perceptions of RCA, (3) challenges in RCA, (4) hybrid training and (5) future perspectives. Participants felt the RCA training was useful and broadened their understanding in incident investigation. More in-depth training in interviewing skills, report writing with practical sessions could further enhance their competencies in RCA. Participants accepted the use of hybrid online–offline training well. Most participants would welcome an independent organisation to conduct RCA as findings would be more objective and recommendations more effective.Conclusions This study provided an evaluation on the effectiveness of a hybrid RCA training course. Healthcare and training organisations can consider this training mode as it could reduce the cost of training and enhance flexibility in course arrangement while preserving quality and effectiveness. Virtual focus groups to interview participants were found to be convenient as it minimised travelling time and onsite arrangement while maintaining the quality of discussion.